Pengaruh Disiplin Kerja Dan Model Kepemimpinan Terhadap Kinerja Karyawan Pada PT Antilope Madju Puri Indah - Salsabillah; Usran Masahere (PT. Pustaka Cendekia Publisher, 2024)
In the modern era, competition in business is getting tighter and fiercer. Human resources are one of the most essential parts of a company, especially at PT Antilope Madju Puri Indah. This research was conducted to determine the influence of work discipline and leadership models on employee performance. The method used is a quantitative statistical method. The analytical tool used was Spss Statistics 26; in this study, 60 respondents were used as the research population, the research sample used a saturated sampling technique, and questionnaires were used as a data collection tool. From the validity test and reliability test of the work discipline variable and leadership model, the results of the validity test are said to be valid because the calculated r-value> r table and the reliability test results are said to be reliable with the Cronbach alpha value calculated r 0.773 > r table 0.60. The results of the determination test have an Adjusted R square value of 0.588 or 58.8%, so the variables of work discipline and leadership model influence 58.8% of employee performance; the remainder is influenced by other variables not studied. The F test shows a Fcount value of 43,137 > Ftable 3.15. Therefore, it can be concluded that work discipline and leadership models simultaneously influence employee performance.